Torsional Alfvén waves in solar magnetic flux tubes of axial symmetry - Murawski K.; Solov'Ev A.; Musielak Z.E.; Srivastava A.K.; Kras̈kiewicz J. (My University, 2025)
Aims. Propagation and energy transfer of torsional Alfvén waves in solar magnetic flux tubes of axial symmetry is studied. Methods. An analytical model of a solar magnetic flux tube of axial symmetry is developed by specifying a magnetic flux and deriving general analytical formulas for the equilibrium mass density and gas pressure. The main advantage of this model is that it can be easily adopted to any axisymmetric magnetic structure. The model is used to numerically simulate the propagation of nonlinear Alfvén waves in such 2D flux tubes of axial symmetry embedded in the solar atmosphere. The waves are excited by a localized pulse in the azimuthal component of velocity and launched at the top of the solar photosphere, and they propagate through the solar chromosphere, the transition region, and into the solar corona. Results. The results of our numerical simulations reveal a complex scenario of twisted magnetic field lines and flows associated with torsional Alfvén waves, as well as energy transfer to the magnetoacoustic waves that are triggered by the Alfvén waves and are akin to the vertical jet flows. Alfvén waves experience about 5% amplitude reflection at the transition region. Magnetic (velocity) field perturbations that experience attenuation (growth) with height agree with analytical findings. The kinetic energy of magnetoacoustic waves consists of 25% of the total energy of Alfvén waves. The energy transfer may lead to localized mass transport in the form of vertical jets, as well as to localized heating because slow magnetoacoustic waves are prone to dissipation in the inner corona. © 2015 ESO.